ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI PURSED LIP BREATHING TERHADAP TINGKAT KELETIHAN (FATIGUE) PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS - Dinar Aufia Fadilla Hakim (2023)
Chronic Kidney Disease (CKD) is a condition in which the kidneys experience a progressive decline in function and cannot return to normal, characterized by the presence of urea in the urine (uremia) or a glomerular filtration rate (GFR) of less than 60 ml/minute. /1.73 m² in the last three months. Patients with chronic kidney disease need kidney replacement therapy to replace kidney function in the body, one of them is dialysis (Hemodialysis). Hemodialysis that lasts a long time has an impact on the physical and psychological of the patient, one of which is fatigue. One of the interventions to overcome fatigue is Pursed Lip Breathing. The purpose of providing this nursing care is to determine the effect of Pursed Lip Breathing on the level of fatigue in patients with chronic kidney disease undergoing hemodialysis. Measuring the level of fatigue using the Visual Analogue Fatigue Scale (VAFS). The results of providing nursing care showed that the patient's fatigue level decreased by 4.6 cm (7.2 cm before and 2.6 cm after the intervention) in two meetings for one week. It can be concluded that Pursed Lip Breathing therapy is effective for overcoming fatigue (fatigue) in chronic kidney disease patients undergoing hemodialysis. Keywords: Fatigue, Chronic Kidney Disease, Hemodialysis, Pursed Lip Breathing